Outcome of stapled haemorrhoidopexy versus open haemorrhoidectomy in grade third and fourth haemorrhoids - Gani, Mubashir; Illahi, Mir Fazil; Wani, Rauf A.; Chowdri, Nisar Ahmad (International Surgery Journal, 2024)
Background: Haemorrhoids are one of the most common benign anorectal problems worldwide. Methods: This study was conducted in the department of General Surgery, Sher e Kashmir Institute of Medical Sciences and SKIMS Medical College from April 2021 to October 2022. The study included 80 patients which were randomly divided into two groups. Group A was offered Stapled Haemorrhoidopexy and Group B underwent open hemorrhoidectomy. All relevant data was collected and final inferences were drawn Results: In our study there were 80 patients with mean age of 45 years with male preponderance. Majority of patients were having duration of symptoms for 6-12 or >12 months. The most common presenting complaint was prolapsed mass, followed by bleeding per rectum. 50 patients had grade 3, 30 patients had grade 4 haemorrhoids. Mean operative blood loss, operative time, wound healing time and mean duration of hospital stay was less in MIPH group. Post procedure complications were present in 12 patients in group A and 32 patients in group B. Most common complication in group B was urinary retention. There was no recurrence in both groups up to 6 months. Post-operative pain was significantly less in MIPH group. Conclusions: Stapled Haemorrhoidopexy has less, post-operative pain, operative time, hospital stay, complications and less wound healing time. However, there is no significant difference in long term complications when compared with Miligan-Morgan technique. Cost of Stapler gun used for MIPH may be a limiting factor.